2016
DOI: 10.5430/ijhe.v5n3p222
|View full text |Cite
|
Sign up to set email alerts
|

The Key Predictors of Success in University in France: What Are the Contributing Factors and Possible New Directions in Educational Research?

Abstract: In France, the university has been experiencing a major crisis for several decades in the form of a high rate of student failure, particularly during the licence, or first cycle of studies. This prolonged crisis has led educational researchers to focus on the predictors of student failure in University. This paper reviews the existing literature on both student failure and success in University in the French context. We first conduct a thorough analysis of the various factors explaining failure rates, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
8
0
4
Order By: Relevance
“…Self-efficacy beliefs are essential for professional students, as they one of the key predictors of academic performance [ 26 , 27 ]. Self-efficacy in leading a research is vital for an individual to succeed in research-related field.…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy beliefs are essential for professional students, as they one of the key predictors of academic performance [ 26 , 27 ]. Self-efficacy in leading a research is vital for an individual to succeed in research-related field.…”
Section: Introductionmentioning
confidence: 99%
“…Mentors should be assigned to new generation researchers to help write research reports for presentations at academic conferences or publish in journals. Duguet, Mener, & Morlaix (2016) found that educational research is the key predictor of success in universities in France.…”
Section: Discussionmentioning
confidence: 99%
“…Les études mettent en évidence un effet de la série du baccalauréat, de la mention et du retard scolaire. Ainsi, être titulaire d'un baccalauréat professionnel ou technologique, ne pas avoir obtenu son baccalauréat avec mention ou encore s'inscrire à l'université avec un retard scolaire augmentent la probabilité d'échec (Beaupère & Boudesseul, 2009 ;Morlaix & Suchaut, 2015 ;Duguet & al., 2016).…”
Section: Scolaires Ou Cognitifsunclassified